Communication between parents and adolescent children on health behaviors - Alvarez Aguirre, Alicia (2021)
Today, the adolescent lives its interpersonal relationships mediated by social networks and socially conducted towards the taking of risk behaviors, motivated from power and acceptance by their peer environment.  This circumstance highlights the importance of parents, such as these significant people who will have to introduce in adolescent values ​​and behaviors that promote their biopsychosocial development.  Hence, communication between parents and children is a key and fundamental part, since assertive and affective dialogue will facilitate the exchange of experiences that will be useful to the adolescent when making decisions.  The detail before this, is that academic and scientific evidences that this communication is not carried out, leaving the adolescent devoid of elements that would contribute to the growth and personal development of it.  So in the following essay, a reflection on communication between parents and adolescent children is deployed regarding health behaviors. Keywords: parents, adolescence, communication, assertiveness